2015
DOI: 10.1016/j.ygeno.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and evolution of cotton fiber development genes in the fibreless Gossypium raimondii genome

Abstract: Cotton fiber represents the largest single cell in plants and they serve as models to study cell development. This study investigated the distribution and evolution of fiber Unigenes anchored to recombination hotspots between tetraploid cotton (Gossypium hirsutum) At and Dt subgenomes, and within a parental diploid cotton (Gossypium raimondii) D genome. Comparative analysis of At vs D and Dt vs D showed that 1) the D genome provides many fiber genes after its merger with another parental diploid cotton (Gossyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…The correlation observed among fiber quality traits may be the direct result of colocalization of fiber quality QTLs. Similar results were previously reported in cotton (Jiang et al, 1998;Paterson et al, 2003;Mei et al, 2004;Chee et al, 2005b;Rong et al, 2007;Yu et al, 2013;Xu et al, 2015), where the genetic control of fiber quality by the D t subgenome was significantly greater than that of A t subgenome. Another noteworthy observation is that 16 (or 57%) of the fiber quality QTLs were identified on D t subgenome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation observed among fiber quality traits may be the direct result of colocalization of fiber quality QTLs. Similar results were previously reported in cotton (Jiang et al, 1998;Paterson et al, 2003;Mei et al, 2004;Chee et al, 2005b;Rong et al, 2007;Yu et al, 2013;Xu et al, 2015), where the genetic control of fiber quality by the D t subgenome was significantly greater than that of A t subgenome. Another noteworthy observation is that 16 (or 57%) of the fiber quality QTLs were identified on D t subgenome.…”
Section: Discussionsupporting
confidence: 91%
“…Although the D subgenome progenitor did not produce spinnable fibers, it has loci that influence the quality of the fiber produced in allotetraploid cottons, which indicates that the polyploidization of Gossypium has given rise to novel variation for fiber quality traits (Jiang et al, 1998;Wendel, 2000). Similar results were previously reported in cotton (Jiang et al, 1998;Paterson et al, 2003;Mei et al, 2004;Chee et al, 2005b;Rong et al, 2007;Yu et al, 2013;Xu et al, 2015), where the genetic control of fiber quality by the D t subgenome was significantly greater than that of A t subgenome.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, they did not have the same contribution to G. hirsutum, especially in fiber-and stress-associated TFs. The findings in this study for TFs are in accordance with another that reported that A and D genomes do not equally contribute and D genome (G. raimondii) provides more genes than A genome (G. arboreum) (Xu et al 2015). Therefore, they might share less genes with each other than with G. hirsutum.…”
Section: Comparison Of Transcription Factors Of Gossypium Species Revsupporting
confidence: 92%
“…In the case of G hirsutum, D-genome has a significant association of QTLs related to adaption i.e., BOD, DF, and FY, while A-genome has comparatively more associations for traits related to fiber quality. These results are in line with the A and D genome evolution (Xu, Yu et al, 2015).…”
Section: Genetic Differentiation Between G Purpurascens and Cultivatsupporting
confidence: 88%